Bust of the wife of Lev Tolstoj made by her son. The bust is being exhibited at the Doré Galleries, where it forms part of a representative display by a hunderd leading Russian artists. From: The Observer 1910, november 20 - Tolstoj, ...,
Bust of the wife of Lev Tolstoj made by her son. The bust is being exhibited at the Doré Galleries, where it forms part of a representative display by a hunderd leading Russian artists. From: The Observer 1910, november 20.